The Tyranny of the Clock. - Sutherland, Ivan (Communications of the ACM, 2012)
The author mentions the computer scientist Alan Turing and argues that clocked synchronization of computer programs inhibits communication efficiency and information transmission, focusing on research in clock-free computer programming. According to the author, communication rather than logic should dominate digital design paradigms, given the costs of wires in circuit chips. Topics include software development, optimization, and computer performance.